Comment on "Oestrogen-induced angiogenesis and implantation contribute to the development of parasitic myomas after laparoscopic morcellation" - Ospan A. Mynbaev; Antonio Malvasi; Sergei S. Simakov; Andrea Tinelli (BMC, 2017)
Abstract Background The cause of contamination and dissemination of leiomyoma tissue particles and cells in the peritoneal cavity during myomectomy is a challenging issue for both clinicians and researchers. Therefore, the article by Huang et al. recently published in your journal is the subject of this letter. Main body We comment on the role of laparoscopic condition in xenograft implantation and also highlighted the shortcomings of this study. The surgical technique of intramural fibroid enucleation, cell spillage during morcellation and postsurgical hormonal impact on the development of parasitic myomas become evident, while the contribution of CO2 insufflation, the fibroid's nature, mutations and pseudocapsule impacts on angiogenesis are not clear. In addition, an exploration of the exact origin of implanted fragments harvested from the fibroid tissue and their nature might play a significant role in the implantation and the angiogenesis induction ability of xenografts. Conclusion Taking into account the current literature in the scope of this study, we suggest that the factors involved in development of parasitic myomas can be classified as confirmed and doubtful contributions.